Efektivitas Rehabilitasi sebagai Alternatif Hukuman bagi Pecandu Narkoba (Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika) - Yuliana Yuli Wahyuningsih; Atik Winanti; Marina Ery Setyawati; Kayus Kayowuan Lewoleba; Satino Satino (Pusat Riset dan Inovasi Nasional, 2026)
Law Number 35 of 2009 concerning Narcotics provides legal space for drug addicts to receive rehabilitation as an alternative to imprisonment. This policy aims to restore addicts' condition so they can return to normal life and reduce overcrowding in correctional institutions. This study aims to analyze the effectiveness of implementing rehabilitation as a form of alternative punishment for drug addicts, both from a legal and practical perspective. The method used is normative legal research with a legislative approach and empirical studies in several rehabilitation institutions and law enforcement institutions. The results of the study indicate that although normative legal provisions already accommodate rehabilitation, in practice there are still various obstacles such as minimal coordination between agencies, a lack of facilities and infrastructure, and low public legal awareness. Therefore, strengthening regulations, increasing the capacity of rehabilitation institutions, and consistent law enforcement are needed so that rehabilitation can be an effective solution in dealing with drug abuse. Therefore, strengthening regulations, increasing the capacity of rehabilitation institutions, and consistent law enforcement are needed so that rehabilitation can be an effective solution in dealing with drug abuse.